The Study of Solar Incident on Planar Surface for Kinetic Art - Waiyawat Saitum (IJCAS (International Journal of Creative and Arts Studies), 2017)
In future, renewable energy will become mainstream global energy source because it flows all the time, also the solar energy. The sun always directly emits light through the earth, depending on how we utilize it. The study will fill the gap that the most of photovoltaic panel facing to the same direction against solar incident for maximum efficiently. It would be better if photovoltaic appliance to have aesthetic and capability in the same time. But changing planar surface angle for artistic purpose also need to consideration of efficiency for solar energy. The purpose of this study is to explore the most appropriate angle of solar incident that impacts directly to the planar surface, which will leads to gain maximum electric energy from photovoltaic cell. The variation angle of planar surfaces will be discovered could possibly produce energy to be applied for any purposes. The additional sources of other renewable energy gadgets may install to generate more electric power. These planar surfaces can be composited together into many new shapes and forms for researcher to create more impressive artwork. In this study, the chosen material was Monocrystalline solar cell (mono-Si) to generate energy, wood and glass for kinetic sculpture. The procedures of study were as follow: 1. Specific location by Latitude will be achieved I. Altitude II. Seasons III. Sunlight direction IV. Sunrise and Sunset time 2. Calculate Solar radiation from each Photovoltaic cell for energy gain. 3. Compares output energy and mechanic usage for Kinetic Art 4. Increases capability of solar incident by improving angle of planar surface or multiply. Results of this research will be the search of artistic identity in art forms, it will be guideline for designers to develop potential Kinetic arts and or further creative works.